2021
DOI: 10.1002/jemt.23774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different remineralizing agents on color stability and surface characteristics of the teeth following vital bleaching

Abstract: The aim of the study was to investigate the effects of various remineralizing agents on the color stability and surface characteristics of the teeth after vital bleaching. The extracted 96 human incisors were used for the study. Initially, the samples were randomly divided into two groups and exposed to in‐office and at‐home bleaching agents. Then, the groups were divided into six subgroups (n = 8), including the control group did not undergo remineralization after bleaching, according to five remineralizing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Additional analyses based on optical profilometry will include a quantitative evaluation of enamel’s surface roughness. Contrary to these findings, others [ 7 , 12 ] have shown that enamel surface properties were negatively impacted by bleaching protocols modulated by high-concentrated bleaching gels (either 30% or 40% HP), independently of their pH values (either acidic or neutral), using similar AFM techniques. Therefore, it could be assumed that the compositions tested have the potential to resolve mild-to-severe dental discolorations without negatively impacting the chemical arrangement or surface properties of treated enamel.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Additional analyses based on optical profilometry will include a quantitative evaluation of enamel’s surface roughness. Contrary to these findings, others [ 7 , 12 ] have shown that enamel surface properties were negatively impacted by bleaching protocols modulated by high-concentrated bleaching gels (either 30% or 40% HP), independently of their pH values (either acidic or neutral), using similar AFM techniques. Therefore, it could be assumed that the compositions tested have the potential to resolve mild-to-severe dental discolorations without negatively impacting the chemical arrangement or surface properties of treated enamel.…”
Section: Discussionmentioning
confidence: 84%
“…Even though several reports have demonstrated the bleaching efficacy of IPB [ 4 , 5 , 6 ], other studies have indicated that the utilization of these highly caustic bleaching agents may result in the occurrence of adverse effects (short- and long-term), including irreversible changes in enamel topography [ 7 ] and chemical make-up [ 8 , 9 , 10 ], decreased surface microhardness [ 11 ], increased surface roughness [ 12 ], diminished bond strength [ 13 ], and reduced fracture resistance [ 14 ]. From the clinical standpoint, the most prevalent adverse effect reported by patients and clinicians is mild to severe dentin hypersensitivity (DH) [ 4 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Every sample was sanded using the same technique with new carbide silicon abrasive paper. 11 The samples spent ten minutes in an ultrasonic machine to remove residues. 16 By measuring the distance between the incisal edge and the cementoenamel junction, and the mesiodistal dimension, the middle third of the labial surface of the crown was marked using a caliper.…”
Section: Methodsmentioning
confidence: 99%
“…9 This significantly lowers mineral loss and restores microhardness and roughness. 11 The objectives of the following study are to assess the impact of fluoridated dental products (toothpaste, mouth rinse, and fluoride varnish) on bleached tooth enamel's surface roughness and surface morphology when used before, after, or before and after the tooth bleaching process.…”
Section: Introductionmentioning
confidence: 99%
“…After the bleaching protocols were completed, the specimens were immersed in coffee prepared with 2 g of instant coffee powder (Nescafé Classic, Nestlé, Vevey, Switzerland) and 200 mL of boiling distilled water for 30 min per day for two weeks [ 15 ]. The solution was prepared freshly every day.…”
Section: Methodsmentioning
confidence: 99%